Analysis of Anopheles spp mosquito density result Cattle Barrier Intervention in Malaria Endemic Villages Banyumas 2012 (Efforts Accelerate Achievement of MDG's 2015 by Termination Chain Transmission) - Aris Santjaka; Djamaluddin Ramlan; Elsye Rimimper (Jurnal Riset Kesehatan, 2013)
Malaria eradication program currently with two aspect mainly is one aspect decided chain vector and plasmodium transmission, so not next transmission. In fact a lot mosquitoes out of the house than inside the house, but the sprayingis done event in the house, some research suggests it 97,96% mosquitoes outside the house (Santjaka A, 2010), precipitin test 0,53 to 2,29% anthrophophilic (Bangs, 1989) to An.barbirostris 1,47% (Munif, Sudomo, Soekarno, 2007). Thus, spraying inside the house should be reconsidered.This study to answer the anomalous this fact, by doing long lasting insecticide nets in cattle and also it to map mosquitoes anopheles Spp, density and delatation. The research method used was pre experimental design with pre and post test is by giving mosqitoes was 98,7% were Anminimus and maculatus, and the rest An.kochi and An.vagus. 73,3% of mosquitoes cought in the cage. Conditions delatation36,36% one delatation, nulliporous rest, so it canbe said to include young mosquitoes.